The Role of Islamic Religious Education Teachers in Improving Student Discipline in Congregational Prayers at Madrasah Ibtidaiyah Negeri 5 Boyolali - Solikhah; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
This research aims to determine the extent of the role of Islamic religious education teachers in improving the discipline of students praying in congregation at MIN 5 Boyolali. This research is a qualitative research. This research was conducted at MIN 5 Boyolali from October to December 2023. The subjects in this research were Islamic Religious Education Teachers, school principals, student affairs officers and students of Madrasah Ibtidaiyah Negeri 5 Boyolali. Data was obtained using participant observation, structured interviews, and documentation. Data analysis uses the Miles and Huberman analysis model called interactive analysis. This analysis is divided into several stages: data collection, data reduction, data presentation, and drawing conclusions. The results show that the role of Islamic religious education teachers is as educators, teachers, mentors, trainers and advisors in the discipline of students praying in congregation. Then the kultum after congregational prayers is carried out in a series of congregational noon prayers. And as a cult official, the madrasah brings in high school students around the school location as lecturers.